Chickens Expressing IFIT5 Ameliorate Clinical Outcome and Pathology of Highly Pathogenic Avian Influenza and Velogenic Newcastle Disease Viruses - Rohaim, Mohammed A.; Santhakumar, Diwakar; Naggar, Rania F. El; Iqbal, Munir; Hussein, Hussein A.; Munir, Muhammad (Frontiers in Immunology, 2018)
Innate antiviral immunity establishes first line of defence against invading pathogens through sensing their molecular structures such as viral RNA. This antiviral potential of innate immunity is mainly attributed to a myriad of IFN-stimulated genes (ISGs). Amongst well-characterized ISGs, we have previously shown that antiviral potential of chicken IFN-induced proteins with tetratricopeptides repeats 5 (chIFIT5) is determined by its interaction potential with 5’ppp containing viral RNA. Here, we generated transgenic chickens using avian sarcoma-leukosis virus (RCAS)-based gene transfer system that constitutively and stably express chIFIT5. The transgenic chickens infected with clinical dose (EID50 104 for HPAIV and 105 EID50 for vNDV) of high pathogenicity avian influenza virus (HPAIV; H5N1) or velogenic strain of Newcastle disease virus (vNDV; Genotype VII) showed marked resistance against infections. While transgenic chickens failed to sustain a lethal dose of these viruses (EID50 105 for HPAIV and 106 EID50 for vNDV), a delayed and lower level of clinical disease and mortality, reduced virus shedding and tissue damage was observed compared to non-transgenic control chickens. These observations suggest that stable expression of chIFIT5 alone is potentially insufficient in providing sterile protection against these highly virulent viruses; however, it is sufficient to ameliorate the clinical outcome of these RNA viruses. These findings propose the potential of innate immune genes in conferring genetic resistance in chickens against highly pathogenic and zoonotic viral pathogens causing sever disease in both animals and humans.